Guideline for the diagnosis, treatment and response criteria for Bing-Neel syndrome - Minnema, Monique C.; Kimby, Eva; D’Sa, Shirley; Fornecker, Luc-Matthieu; Poulain, Stéphanie; Snijders, Tom J.; Kastritis, Efstathios; Kremer, Stéphane; Fitsiori, Aikaterini; Simon, Laurence; Davi, Frédéric; Lunn, Michael; et al. (Haematologica (Roma), 2017)
Bing Neel syndrome is a rare disease manifestation of Waldenström's macroglobulinemia that results from infiltration of the central nervous system by malignant lymphoplasmacytic cells. In this guideline we describe the clinical symptoms, as well as the appropriate laboratory and radiological studies, that can aid in the diagnosis. The presentation of Bing Neel syndrome may be very diverse, and includes headaches, cognitive deficits, paresis, and psychiatric symptoms. The syndrome can present in patients with known Waldenström's macroglobulinemia, even in the absence of systemic progression, but also in previously undiagnosed patients. Diagnostic work-up should include cerebral spinal fluid analysis with multiparameter flow cytometry to establish B-cell clonality, protein electrophoresis and immunofixation for the detection and classification of a monoclonal protein as well as molecular diagnostic testing for immunoglobulin gene rearrangement and mutated MYD88. MRI of the brain and spinal cord is also essential. The second challenge is to expand our knowledge of prognosis and treatment outcome. Prospective clinical trials on Bing Neel syndrome patients that employ uniform treatment along with appropriate laboratory cerebral spinal fluid assessments and standardized MRI protocols will be invaluable, constituting a significant step forward in delineating treatment outcome for this intriguing disease manifestation.